INFLUENCE EARNING QUALITY AND LIQUIDITY OF COST OF CAPITAL - Nanik Lestari; Umi Rahayu (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2017)
This study was conducted to investigate the effect of earnings quality and liquidity of the capital costs. To measure earnings quality is done by using Discretionary Accrual using modified Jones models (Dechow et al, 1995), while liquidity is measured using liquidity risk. The sample used in this study was 290 company listed on the Indonesia Stock Exchange in 2010-2014, using simple regression to determine the effect of earnings quality and liquidity of the capital costs. Based on the results of the hypothesis in this study, showing that (1) the quality of earnings significantly negative effect on the cost of capital, (2) liquidity no significant effect on the cost of capital, (3) control variables used are not effect information asymmetry towards the cost of capital.